2002
DOI: 10.1038/sj.jim.7000302
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fluid shear on the structure and material properties of sulphate-reducing bacterial biofilms

Abstract: Biofilms of sulphate-reducing Desulfovibrio sp. EX265 were grown in square section glass capillary flow cells under a range of fluid flow velocities from 0.01 to 0.4 m/s (wall shear stress, tau(w), from 0.027 to 1.0 N/m(2)). In situ image analysis and confocal scanning laser microscopy revealed biofilm characteristics similar to those reported for aerobic biofilms. Biofilms in both flow cells were patchy and consisted of cell clusters separated by voids. Length-to-width ratio measurements (l(c):w(c)) of biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 22 publications
4
38
0
1
Order By: Relevance
“…43 Studies on biofilm mechanical properties have established a link between hydrodynamics, biofilm structure, and strength. 44,45 In general, the higher the flow velocities the greater the nutrient flux towards the biofilm due to a diminished external resistance to the boundary layer. 46 Computational simulations revealed that at Re ¼ 13.3, the biofilms remained thin, suggesting that the higher the Re the stronger the forces that the biofilm must resist.…”
Section: Morphological Variation Of Initial Biofilm Formationmentioning
confidence: 99%
“…43 Studies on biofilm mechanical properties have established a link between hydrodynamics, biofilm structure, and strength. 44,45 In general, the higher the flow velocities the greater the nutrient flux towards the biofilm due to a diminished external resistance to the boundary layer. 46 Computational simulations revealed that at Re ¼ 13.3, the biofilms remained thin, suggesting that the higher the Re the stronger the forces that the biofilm must resist.…”
Section: Morphological Variation Of Initial Biofilm Formationmentioning
confidence: 99%
“…The influence of the model parameters on the patterns is investigated in more detail by means of the two-dimensional reduction. The evolution of the patterns with some parameters seems to follow qualitative trends experimentally observed by other groups [36,[39][40][41][42][43] and by ourselves [44]. However, the effect of mechanical processes like displacement of cell aggregates due to external forces, thought to be relevant in the dynamics of real biofilm patterns such as streamers, must yet be accounted for.…”
Section: Introductionmentioning
confidence: 57%
“…As the Reynolds number increases, turbulent effects play a role and the particle deposition rate increases linearly with the Reynolds number for small Stokes numbers [63]. It has been experimentally observed that the residence time of bacteria hitting a wall increases with shear [30] and that biofilm accumulation tends to be larger for larger flows [42]. Thus, γ (Re) is likely to increase with Re.…”
Section: E Adhesion Of Floating Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast to solids under tensile strength, where fracture occurs after the yield point, viscoelastic materials show necking or thinning, which may be the origin of the collapsed threads observed after separation for the EPS-producing strain (Alpkvist et al 2006). Dunsmore et al (2002) described a very similar yet distinctly different process for biofilms grown under high and low flow, showing formation of so-called 'streamlined' biofilm clusters under high flow.…”
Section: Separationmentioning
confidence: 99%